Advanced plant disease diagnostic training: an international short course - Miller, S.A.; Lapaire Harmon, C.; Arévalo, M.; Beed, Fenton D.; Kinyua, Z.M.; Tolin, S.A.; Xin, J. (2008)
As a part of its commitment to disease diagnostic capacity development, the IPM CRSP Global Theme on Regional Diagnostic Laboratories developed and sponsored an international short course entitled “Intensive Training in Plant Disease Diagnostics”, held August 26 - September 9, 2007 at The Ohio State University in Wooster, OH. The curriculum included the following topics: sampling, train-the-trainer programs, the art and science of plant disease diagnosis, monitoring for high risk pathogens, distance diagnostics, the Clinic Information Management System and Distance Diagnostic and Identification System(CIMSDDIS), developing standard operating protocols, classical diagnosis of bacteria, fungi, oomycetes, viruses and nematodes, internet information sources, introduction to SanitaryPhytosanitary issues, and advanced diagnostic techniques. Lecture topics were supported by hands-on laboratory and field experiences. A two-day trip to the USDA Animal and Plant Health Inspection Service (APHIS) laboratories in Riverdale, MD, allowed participants to meet with APHIS researchers and learn about the structure and function of the organization. A total of 25 scientists from 14 countries completed the course.